The Image of Vlachs in the works of Georgios Akropolites - Kotłowska, Anna (Balcanica Posnaniensia. Acta et studia, 2021)
The writings of Georgios Akropolites, both in historiography as well as in rhetoric, do not contain much information about Vlachs. Their presence is always secondary to the description of other events, judged through the perspective of the interests of the Palaiologan dynasty. Nevertheless, the few references to Vlachs are of significant value from the point of view of historical geography, being helpful especially when it comes to understanding the application of the term of so-called “Vlachia” (in different variations) to certain areas of northern and western Greece. Presented paper contains: a) an overview of the entire works of Georgios Akropolites, b) translated excerpts from Akropolites' main work History, together with a philological and historical commentary, c) an annex containing notes on significance of references to Vlachs in the literary masterpiece of the Cretan Renaissance, the Erotokritos written by V. Kornaros, for historical research.